Expanding smallholder irrigation in central Kenya demonstrates the importance of protecting grassland landscapes - Hacheme, Gilles Quentin; Wood, Stephen Andrew; Magesa, Renatus; Tadesse, Girmaw Abebe; Robinson, Caleb; Peter, Elizah; Kipkoech, Elkanah; Sainepo, Bernice (IOP Science - Environmental Research Letters, 2025)
The rapid expansion of agriculture in Kenya, driven by the country's growing population, poses critical environmental challenges such as climate change and biodiversity loss. While deforestation has received much attention, the equally vital grasslands are under significant threat. Monitoring efforts have often prioritized the extent of land conversion, with limited focus on the intensity of conversion, particularly in non-forest biomes. This study addresses this gap by assessing the expansion of row crop and irrigated agriculture in the grasslands of central Kenya from 2018 to 2022. The region, particularly around Laikipia County, has seen a rapid increase in irrigated agriculture, encroaching on natural grasslands and threatening local wildlife through excessive water extraction. We mapped the expansion of both smallholder and large-scale croplands and developed a model based on vegetation indices and proximity to key water sources to estimate irrigation likelihood. Our results show a 27% increase in likely irrigated croplands from 2018 to 2022, with projections indicating that, if current trends persist, irrigation areas will double by 2030, probably increasing water consumption substantially. This study underscores the urgent need to protect Kenya's native grasslands, which are facing active threats with far-reaching environmental consequences.